Arginase inhibitory properties of flavonoid compounds from the leaves of Mulberry (Morus alba, Moraceae). (4th June 2020) - Arraki, Kamel; Totoson, Perle; Attia, Rym; Zedet, Andy; Pudlo, Marc; Messaoud, Chokri; Demougeot, Céline; Girard, Corine
Abstract: Objectives: We aimed to isolate and identify bioactive molecules from Morus alba (Moraceae) leaves having arginase inhibitory activity towards the combat of clinical outcomes related to endothelial dysfunction. Method: Extraction and isolation were carried out by successive macerations, prepurification by using a Solid Phase Extraction (SPE) and separation using preparative PLC. The structures of the isolated components were established and confirmed by spectroscopic analyses, including the ESI-HRMS and NMR spectroscopic investigations. Biological evaluation was performed by using an in vitro assay with liver bovine purified arginase and by an ex vivo aortic ring study. Key findings: We demonstrated that a phenolic extract from the leaves of M. alba possesses mammalian arginase inhibitory capacities. Investigation of the chemical constituents of its leaves results in the isolation and identification of ten compounds investigated in vitro for their arginase inhibitory capacities. Four compounds showed significant inhibition of arginase, with percentage inhibition ranging from 54% to 83% at 100 µm . In isolated rat aortic rings incubated with NO synthase inhibitor, Luteolin-7-diglucoside compound (2 ) was able to increase acetylcholine-induced relaxation. Conclusions: These results demonstrated the attractive ability of M. alba to be a potential source for the discovery of new active products on vascular system.